Analisis Kinerja Keuangan Dengan Menggunakan Metode Du Pont System Pada PT. Astra International, Tbk Periode 2013-2017 - Lilipory, Novita Veronika; Taroreh, Henny S.; Mangindaan, Joanne V. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
This study aimed to determine the financial performance of PT. Astra International, Tbk using the Du Pont System method in the period 2013-2017. Du Pont analysis is a method in a modified profitability ratio that includes two analysis ratios, namely Return on Investment and Return on Equity. This study uses a type of descriptive evaluative research with a quantitative approach; the data sources used are secondary data with documentation data collection techniques. Based on the results of data analysis it was concluded that Return On Investment PT. Astra International, Tbk tends to experience volatility or fluctuations from 2013 to 2017, which are indicated through changes in value on the net profit margin and total assets turnover. Return on Equity PT. Astra International, Tbk also tends to experience volatility or fluctuations from 2013 to 2017, seen from the fluctuating level of capital utilization of shareholders in financing a number of company assets. These two ratios underlie the importance of companies to conduct evaluations and overall innovation on the company's financial condition, including the utilization of assets and utilization of equity so that the company's profitability can remain controlled.